ARAH PENGEMBANGAN SUMBERDAYA MANUSIA DALAM DIMENSI PENDIDIKAN ISLAM - Warul Walidin (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2016)
This paper offers a solution to improve the quality of human resources through education Islam. Humans are the central points that are the subject and development engineers as well as objects that are engineered and enjoy the fruits of development. In addition, humans are also the only creatures that have the potential to develop themselves through their knowledge. Efforts to develop and improve the quality of human resources can be done through various means, including through education. This education is the path of improving the quality of human resources is more emphasis on the establishment of basic quality, such as faith and piety, personality, intelligence, discipline, creativity and so on. In Islam the human figure composed of two potential to be built, which is outwardly as the body itself and the spiritual body as the controller. Some aspects of the dimensions that must be considered in the development of human resources, among others, cognitive (knowledge), affective (attitude), and psychomotor (skills) greatly influence the process of formation of one's personality.